Burn depth assessments by photoacoustic imaging and laser Doppler imaging. Issue 2 (24th November 2015) - Ida, Taiichiro; Iwazaki, Hideaki; Kawaguchi, Yasushi; Kawauchi, Satoko; Ohkura, Tsuyako; Iwaya, Keiichi; Tsuda, Hitoshi; Saitoh, Daizoh; Sato, Shunichi; Iwai, Toshiaki
Abstract: Diagnosis of burn depths is crucial to determine the treatment plan for severe burn patients. However, an objective method for burn depth assessment has yet to be established, although a commercial laser Doppler imaging (LDI) system is used limitedly. We previously proposed burn depth assessment based on photoacoustic imaging (PAI), in which thermoelastic waves originating from blood under the burned tissue are detected, and we showed the validity of the method by experiments using rat models with three different burn depths: superficial dermal burn, deep dermal burn and deep burn. On the basis of those results, we recently developed a real‐time PAI system for clinical burn diagnosis. Before starting a clinical trial, however, there is a need to reveal more detailed diagnostic characteristics, such as linearity and error, of the PAI system as well as to compare its characteristics with those of an LDI system. In this study, we prepared rat models with burns induced at six different temperatures from 70 to 98 °C, which showed a linear dependence of injury depth on the temperature. Using these models, we examined correlations of signals obtained by PAI and LDI with histologically determined injury depths and burn induction temperatures at 48 hours postburn. We found that the burn depths indicated by PAI were highly correlative with histologically determined injury depths (depths of viable vessels) as well as with burn induction temperatures. Perfusion values measured by LDI were less correlative with these parameters, especially for burns induced at higher temperatures, being attributable to the limited detectable depth for light involving a Doppler shift in tissue. In addition, the measurement errors in PAI were smaller than those in LDI. On the basis of these results, we will be able to start clinical studies using the present PAI system.